Adverse Events Related to Polyvinyl Alcohol Hydrogel Hemiarthroplasty of 1st Metatarsal: An Analysis of Reports to the United States Food and Drug Administration - Sreenivasulu Metikala MD; Karim Mahmoud Khamis MB, BCh; Kathryn O’Connor MD; Wen Chao MD; Keith L. Wapner MD; Daniel C. Farber MD (Foot & Ankle Orthopaedics, 2020)
Category: Midfoot/Forefoot Introduction/Purpose: Polyvinyl Alcohol Hydrogel (PAH) hemiarthroplasty has gained popularity in the operative management of symptomatic hallux rigidus since its introduction to the US in July 2016. Despite encouraging initial results, any implant has the potential for complications that may not become apparent until it is in widespread use. Also, the series of publications supporting the effectiveness of PAH have come from a limited group of institutions and surgeons which creates an opportunity for observational bias. Other complications or unsatisfactory outcomes may be under-reported, such as those experienced in community centers due to the challenges in publishing lower volume work. In order to look at a broader range of potential complications, we reviewed the United States Food and Drug Administration’s (FDA) database and compared with published literature. Methods: The Manufacturer and User Facility Device Experience (MAUDE) database of the US Food and Drug Administration (FDA) was retrospectively reviewed between July 2016 and October 2019 using the assigned product code: PNW for the PAH implant. All the reported adverse events, implant-related complications, and secondary procedures were analyzed. Results: A total of 49 events have been reported to this voluntary database over the past 3 years while over 22,000 Cartiva devices have been implanted. Implant subsidence was the most common with 16 reported instances. Fragmentation of the device was observed in nine and four reports were related to infection in which two were deep infections needing antibiotic spacers. Bone erosion managed by grafting was documented in three reports and foreign body reaction was noted in one. Persistent pain and swelling were common presentations. Thirty-five of 49 reported events required additional operative procedures performed at a mean interval of 4.75 months following the index procedure while four more were awaiting further surgery. Conversion to fusion was the most common procedure, featured in 10 reports. Conclusion:: The analysis of the MAUDE database disclosed certain device-related dysfunctions that have been under-reported in the published literature. Also, complications such as fragmentation, bone erosion and foreign body reaction have not been previously described. Awareness of these details will assist in decision-making and quality control. Due to the voluntary nature of reporting, the true incidence of each complication is unknown with the above data representing a baseline. Nonetheless, the MAUDE database serves as an illuminating source of information which would further be strengthened by a more robust and mandatory reporting of device-related complications.